2014
DOI: 10.1371/journal.pone.0108284
|View full text |Cite
|
Sign up to set email alerts
|

Understanding of Factors that Enable Health Promoters in Implementing Health-Promoting Schools: A Systematic Review and Narrative Synthesis of Qualitative Evidence

Abstract: Health-promoting schools have been regarded as an important initiative in promoting child and adolescent health in school settings using the whole-school approach. Quantitative research has proved its effectiveness in various school-based programmes. However, few qualitative studies have been conducted to investigate the strategies used by health promoters to implement such initiatives. In this study, the researchers conducted a systematic review and narrative synthesis of the qualitative literature to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
54
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 20 publications
4
54
0
1
Order By: Relevance
“…Many of these findings are congruent with conclusions from other studies examining effective elements of school-based interventions. A recent narrative synthesis of qualitative studies adopting the HPS approach [ 60 ] identified the importance of institutional support, assessment of school needs, ownership of programmes, adequate training and tailoring of intervention components to local contexts. This review also noted the low value placed on health versus academic achievement as a barrier to effective implementation.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these findings are congruent with conclusions from other studies examining effective elements of school-based interventions. A recent narrative synthesis of qualitative studies adopting the HPS approach [ 60 ] identified the importance of institutional support, assessment of school needs, ownership of programmes, adequate training and tailoring of intervention components to local contexts. This review also noted the low value placed on health versus academic achievement as a barrier to effective implementation.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to highly standardized (i.e., prepackaged) intervention programs, that are delivered with high implementation fidelity, the HPS approach is characterized by context sensitivity that requires adaptations to the specific conditions and dynamic processes of a single school [5,14,15]. Due to the complexity of interventions that are rooted in a broader socio-ecological determination of health, a growing need of a "science of delivery" has been demanded that aims to identify elements and dimensions of high-quality implementation [16].…”
Section: Introductionmentioning
confidence: 99%
“…High quality formal communication and peer collaboration are known to contribute to effective implementation in general (Damschroder et al, 2009). Multidisciplinary collaborative approaches and professional networks have also been highlighted as one of five enablers regarding implementation of the health-promoting school concept (Hung, Chiang, Dawson, & Lee, 2014). Networks and pre-existing teams might form a solid basis for shared decision-making, which is important not only for a successful implementation but also for program sustainability (Durlak & DuPre, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…To avoid opposition, staff should be actively involved in detailed planning regarding when and how the programme should be implemented. According to a systematic review on implementation of the concept of health-promoting schools, enthusiasm among staff is maintained if they have a sense of ownership, which can be achieved by letting them play an important role in strategic planning and decision-making (Hung et al, 2014).…”
mentioning
confidence: 99%